Similarities and contradictions in the core logic of three strategy research streams - Lengnick‐Hall, Cynthia A.; Wolff, James A. (Strategic Management Journal, 1999)
The logical foundations shaping three prominent streams of strategic management thought are summarized and then compared and contrasted. The intent is to determine whether these research streams are restatements of a single core logic using different terms to describe the same phenomena and relationships, or whether they provide alternate, and potentially competing, explanations for effective strategic action. Analysis reveals some concordant assertions, some similarities across pairs of frameworks, and some fundamental contradictions among the various logic sets. Since key elements in the fundamental premises of each research stream present logical contradictions with each of the other two, a strategy derived from an integration of these perspectives creates inconsistencies in a firm’s enacted context, its assumptions about strategy making, and its administrative arrangements. As circumstances change, a firm may be required to undergo a ‘core logic shift’ to maintain consistency between its strategy and its strategic context. When a shift becomes necessary, a firm needs to overcome structural inertia, competitive inertia, organizational momentum, and its current management logic to maintain internal consistency. Additional implications of the comparison of these three logics for both theory and practice are discussed. Copyright © 1999 John Wiley & Sons, Ltd.